Spiritual relaxation therapy to improve sleep quality for nurses working shifts who experience sleep problems: a quasi-experimental study - Prasetyo, Sudigdo Dwi; Mukhoirotin, Mukhoirotin (MEDISAINS, 2024)
Background: Impaired sleep quality is a common problem experienced by nurses working shifts, and if not treated properly, it can impact their work performance and overall health. Spiritual Emotional Freedom Technique (SEFT) therapy has been proven to improve sleep quality. However, its effectiveness has never been studied in nurses who experience sleep disorders due to working shifts.Objective: To investigate the influence of spiritual relaxation therapy on sleep quality among nurses experiencing sleep disturbances due to shift work.Method: This is a Quasi-Experimental study with a pre-test-posttest control group design. A total of 38 nurses who experience sleep disorders due to working shifts were included in this study. The PSQI questionnaire was utilized as the instrument to measure sleep quality. Data analysis involved the Mann-Whitney test.Results: The average sleep quality before the intervention was in the mild category; after the intervention, most were in the good category. The results showed that the sleep quality of nurses who received spiritual relaxation was better than the control group (p<0.001).Conclusion: Spiritual relaxation therapy effectively improves the sleep quality of nurses experiencing sleep disturbances due to shift work.